(untitled) (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2024)
To prepare future teachers for the challenges arising from ongoing migration in educational practice, a modular professional development program on the topic of ‚Multilingualism and Education‘ – BIKO-LAMB – has been developed at Leibniz University Hannover. This article focuses on the collaboration of two components within the program – the course Werkstatt DaZ/DaF and its integrated practical application – to shed light on both the higher education didactic perspectives and the possibilities of effectively meeting the needs for high-quality language learning support through interdisciplinary offerings.